2023
DOI: 10.21272/bel.7(2).87-98.2023
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Board Members on the Presence of Pharmacists as Strategic Leaders of Manufacturing Pharmaceutical Companies Operating in South Africa: A Qualitative Study

Ms Nsovo Mayimele,
Patrick Demana,
Mothobi Keele

Abstract: Life-saving medicines are produced by manufacturing pharmaceutical companies (MPCs) with operations worldwide. The COVID-19 pandemic resulted in unequal access to vaccines, which led to advocacy around health rights and MPCs needing to prioritise saving lives over profits. This study aimed to determine the perceptions of board members of the largest listed MPCs in South Africa regarding the presence of pharmacists in the strategic leadership of MPCs, as custodians of medicines. A snowball sampling method was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The role of boards of companies varies across industries, but it typically includes determining the strategy for the organisation. The study further found that the industry offers pharmacists opportunities to enter strategic leadership positions (Mayimele et al, 2023). According to the respondents, all candidates have equal opportunity to be considered for these positions.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…The role of boards of companies varies across industries, but it typically includes determining the strategy for the organisation. The study further found that the industry offers pharmacists opportunities to enter strategic leadership positions (Mayimele et al, 2023). According to the respondents, all candidates have equal opportunity to be considered for these positions.…”
Section: Discussionmentioning
confidence: 81%
“…Mayimele, Demana, and Keele (2023) conducted a qualitative study that had board members of MPCs as key informants in South Africa. The study found few pharmacists in strategic leadership positions in listed medicine product companies (MPCs) in South Africa (Mayimele et al, 2023). However, the respondents of the study, who are in strategic leadership positions, valued the presence of pharmacists.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Singh (2022) notes that the economic growth is based on attracting investment resources to the country. Innovative activity, technological development and improvement of organizational and business processes with the transition to digital technologies are also identified by some researchers as determinants ensuring the economic security of the state (Arivazhagan et al, 2022;Dias et al, 2023;Khalifa et al, 2023;Kliuchnikava, 2022;Houfaf Khoufaf, & Nouiri, 2023;Mayimele, Demana, & Keele, 2023;AL-Hashimi, AL-Toobi, Ahmed, 2023). Some researchers also define the food provision and sufficiency as an important component of the economic security of the state (Irtyshcheva et al, 2023;Čermák and Ligocká, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%